ANTIBODIES TO A UNIQUE REGION IN LYSOZYME PROVOKED BY A SYNTHETIC ANTIGEN CONJUGATE - Arnon, Ruth (1969)
A synthetic conjugate, prepared by covalent binding of a lysozyme fragment (sequence 64-83, denoted „loop” peptide) to a synthetic branched polypeptide, elicited in rabbits the formation of antibodies with specificity directed against a unique region in native lysozyme. These anti-„loop” antibodies were isolated immunospecifically on a lysozyme-cellulose immunoadsorbent. Antibodies with a similar specificity were isolated from antilysozyme sera with an immunoadsorbent prepared from the same „loop” peptide. The capacity of the anti-„loop” antibodies to distinguish between the „loop” peptide, containing a disulfide bridge, and the open-chain peptide derived from it suggests that they are directed against a conformation-dependent determinant.